A study on materialists' preference for cosmetic customisation and impulse purchase tendency in Singapore. - Chua, Hui Ru. (2011)
With the influx of luxury brands into the local retail scene and locals‟ intensifying demand for such brands even in times of recession, Singaporeans seem to be exhibiting increasingly materialistic values. In addition, companies spanning a variety of industries have also jumped onto the bandwagon of offering the option of cosmetic customisation to consumers. Since personal possessions are used in part by materialists to convey their social status, will the concept of cosmetic customisation appeal to them? Given the importance of personal possessions to materialists, will they display impulse purchase tendency? These two questions form the basis of our study.